Inte bara jämställdhet: Beslutet om föräldraledighet, moderskaps- och faderskapsidealoch idéer om barns bästa (Sociologisk Forskning, 2012)
More than gender equality. Decisions on parental leave and ideals around motherhood, fatherhood and the best interest of the child On the basis of 40 semi-structured interviews, this study discusses decision making processes regarding parental leave among nascent first-time middle-class parents in Sweden. We analyze motives and ideas behind the couples’ plans and decisions and how decisions on parental leave were made. We furthermore show how the decision making processes can be discussed in relation to the institutional context. The results show that ideals and norms of gender equality are accompanied by gendered divisions of work and care and a partially traditional view on motherhood and fatherhood. Contrary to previous studies, we do not find a clear link between gender equal ideals and explicit negotiations. An equal division of parental leave is, in some couples, taken for granted to such an extent that the decision on how to divide the leave is taken implicitly rather than explicitly. Decisions on division of parental leave are not isolated processes. Rather, ideals and norms around motherhood, fatherhood, gender equality and not least what is ‘in the best interest of the child’ constitute part of the context in which these decision making processes take place.